2018
DOI: 10.1016/j.ebiom.2018.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Takeda G Protein-Coupled Receptor 5-Mechanistic Target of Rapamycin Complex 1 Signaling Contributes to the Increment of Glucagon-Like Peptide-1 Production after Roux-en-Y Gastric Bypass

Abstract: BackgroundThe mechanism by which Roux-en-Y Gastric Bypass (RYGB) increases the secretion of glucagon-like peptide-1 (GLP-1) remains incompletely defined. Here we investigated whether TGR5-mTORC1 signaling mediates the RYGB-induced alteration in GLP-1 production in mice and human beings.MethodsCirculating bile acids, TGR5-mTORC1 signaling, GLP-1 synthesis and secretion were determined in lean or obese male C57BL/6 mice with or without RYGB operation, as well as in normal glycemic subjects, obese patients with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 46 publications
3
15
0
1
Order By: Relevance
“…60 DCA, a secondary bile acid, is positively correlated with GLP-1, which has a hypoglycemic effect. 61 Although no study yet has confirmed that bile acid can be used as an early predictor and diagnostic marker for T2DM, the results of our study supported that DCA should be further studied. DCA was also proved to be one of the endogenous ligands of Farnesoid X Receptor (FXR) that improved various dysfunctions of glucose, cholesterol, lipid, triglyceride and cholesterol metabolism.…”
Section: Discussionsupporting
confidence: 57%
“…60 DCA, a secondary bile acid, is positively correlated with GLP-1, which has a hypoglycemic effect. 61 Although no study yet has confirmed that bile acid can be used as an early predictor and diagnostic marker for T2DM, the results of our study supported that DCA should be further studied. DCA was also proved to be one of the endogenous ligands of Farnesoid X Receptor (FXR) that improved various dysfunctions of glucose, cholesterol, lipid, triglyceride and cholesterol metabolism.…”
Section: Discussionsupporting
confidence: 57%
“…Microbial treatment of putrescine can produce gamma-aminobutyric acid (GABA), this is an inhibitory neurotransmitter founded in the mammalian central nervous system and is thought to stimulate intestinal cells to release GLP-1 [10]. A 6-week postoperative study demonstrated that deoxycholate-TGR5-mTORC1 signal enhancement contributes to up-regulation of GLP-1 production [11]. An increase in the density of cell population producing incretin (GLP-1 cells, GIP cells, and peptide YY immunoreactive cells) in the jejunum was observed 12 months after RYGB, which provide an anatomical explanation for the increase in GLP-1 plasma levels observed after surgery [12].…”
Section: Glp-1-hindbrain-hypothalamusmentioning
confidence: 99%
“…Es konnte konklusiv Spezies-übergreifend nachgewiesen werden, dass die Serumspiegel zirkulierender biologisch aktiver Gallensäuren nach Roux-en-Y Magenbypass und Schlauchmagen erhöht sind [49,59]. Zhai et al zeigten in Mäusen und Menschen, dass es nach Magenbypass zu erhöhten Konzentrationen von Gallensäuren (insbesondere Deoxycholinsäure), einer vermehrten Expression von TGR5 im Ileum mit einer vermehrten Aktivierung des assoziierten mTORC1 Signalweges und konsekutiv zu einer vermehrten Sezernierung von GLP-1 kommt [60]. Trotzdem muss festgehalten werden, dass diese Arbeit nur Assoziationen und keine mechanistische Rolle der Gallensäuren in der vermehrten Aktivierung der L-Zellen beweist.…”
Section: Postoperative Veränderungen Des Mikrobioms -Möglicher Mechanunclassified